Intrinsic spinal cord lesions complicating epidural anaesthesia and analgesia: report of three cases. Issue 4 (1st April 2002) - Wilkinson, Pa; Valentine, A; Gibbs, J M
Abstract : Serious neurological complications related to epidural anaesthesia and analgesia are only rarely reported. We describe the clinical and radiological features of three patients who sustained intrinsic spinal cord lesions after attempted epidural catheterisation. In each case there was an early onset of motor and sensory impairment after the procedure and MRI demonstrated similar, extensive, paracentral, high signal intensity lesions within the cord on T2 weighted images. Possible mechanisms to explain these MRI appearances are discussed. It is proposed that the most likely cause of these lesions was direct trauma to the spinal cord during the procedure and subsequent injection of fluid into the spinal cord producing localised hydromyelia. The prognosis in each case was for a gradual recovery of motor function but spinothalamic sensory impairment and severe spontaneous pain over the affected area persisted.